The DASH diet in diabetes related complications or comorbidities: an unexpected friend - Liu, Kai; Liu, Shu; Wang, Dong; Qiao, Hong (Frontiers in Nutrition, 2025)
The global epidemic of diabetes and its complications poses a serious challenge to public health. Metabolic disorders and chronic hyperglycemia drive multi-system damage. The application of Dietary Approaches to Stop Hypertension (DASH) diet has been extended from hypertension management to multi-dimensional integrated prevention and treatment of diabetes. DASH diet significantly reduces the risk of type 2 diabetes by optimizing blood glucose homeostasis, reducing hemoglobin A1c (HbA1c), improving insulin sensitivity and insulin resistance, regulating lipid metabolism, and inhibiting oxidative stress and inflammation. In terms of management of complications, the DASH diet reduces the risk of diabetic nephropathy and delays decline of renal function. Its antihypertensive effect and improvement in arterial elasticity synergistically reduce the risk of cardiovascular events. The diet has also shown regulatory potential for metabolic abnormalities in polycystic ovary syndrome and microvascular damage in diabetic retinopathy. The DASH diet is suitable for long-term health management due to its advantages of standardized regimens and multi-target metabolic regulation. Future research needs to focus on molecular mechanisms, individual application optimization, and cross-disease synergies to strengthen the scientific basis and practical value in the comprehensive management of diabetes. This review discusses the multiple abilities by which the DASH diet provides comprehensive protection against diabetes and its complications or comorbidities.